Quantitative estimation of soil wind erosion: possibilities of WEQ - Chornyi, S.G. (AgroChemistry and Soil Science, 2018)
Advantages of using a wind erosion mathematical model (WEQ) for the design for wind erosion control in the conditions of the Ukrainian Steppe was the purpose of the article. The procedures for adapting WEQ to local natural and economic conditions, which will consist in the recalculation of current data on "lumpness" of chernozem and chestnut soils, quantification and mapping of the climatic deflation parameter, and the transfer of all components of the WEQ mathematical model to the metric measuring systemis proposed. Calculations for the adapted model WEQ will need to be compared with soil loss tolerance and in a certain territory such a procedure will be an effective tool for the creation of a scientifically grounded system of soil protection from erosion.